2004
DOI: 10.1592/phco.24.11.1084.36140
|View full text |Cite
|
Sign up to set email alerts
|

Candida kefyr, an Uncommon but Emerging Fungal Pathogen: Report of Two Cases

Abstract: Although Candida species are present as normal microflora of the human host, alterations in host defenses can lead to development of disease. Candida infections, ranging from urinary tract infections to bloodstream infections, are common in patients in the intensive care unit. Infections with non-albicans Candida sp are becoming more frequent, and resistance among these isolates is concerning. Candida kefyr is an uncommonly documented fungal pathogen. We report two cases of infection resulting from C. kefyr in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Colonization and infection follow a seasonal distribution, with higher rates during the warm months of the year. Our understanding of the epidemiology of C. kefyr has been limited, derived mainly from case reports (12,27,28), laboratorybased analyses (13)(14)(15)(29)(30)(31)(32)(33)(34), and large surveillance registries (11). This body of evidence has suggested that HM patients may be a high-risk group for infection with this organism, albeit C. kefyr is a rare cause of invasive disease.…”
Section: Discussionmentioning
confidence: 99%
“…Colonization and infection follow a seasonal distribution, with higher rates during the warm months of the year. Our understanding of the epidemiology of C. kefyr has been limited, derived mainly from case reports (12,27,28), laboratorybased analyses (13)(14)(15)(29)(30)(31)(32)(33)(34), and large surveillance registries (11). This body of evidence has suggested that HM patients may be a high-risk group for infection with this organism, albeit C. kefyr is a rare cause of invasive disease.…”
Section: Discussionmentioning
confidence: 99%
“…The successful treatment with voriconazole of keratitis, retinitis, or chorioretinitis due to Candida spp has also been reported (Granados et al 2004; Jang et al 2005; Varma et al 2005). There are several documented cases of a successful response to voriconazole in the treatment of infections caused by uncommon or fluconazole-resistant species (Corpus et al 2004; Fabry et al 2005): non- C. albicans peritonitis in peritoneal dialysis patients (Kleinpeter 2004), and Candida infection of the subacromial bursa (Khazzam et al 2005). …”
Section: Clinical Use Against Fungal Pathogensmentioning
confidence: 99%
“…andida kefyr (teleomorph: Kluyveromyces marxianus) has been reported as a rare but potentially increasing cause of invasive candidiasis (IC) (1)(2)(3), especially in patients with hematologic malignancies (2,(4)(5)(6). Isolates of this species have been noted to develop reduced susceptibility to echinocandins, although the majority examined in population analyses remain susceptible (7).…”
mentioning
confidence: 99%